Letramentos em diálogo com o acervo do pacto nacional pela alfabetização na idade certa : uma ampliação da experiência com linguagem - Cella, Sirley Morello (My University, 2016)
The challenge of literacy practice in the visual and literary literacy perspective has inspired this study. The discussion focuses the central objective of identifying principles subjacent to didactic sequences proposed by Pacto Nacional pela Alfabetização na Idade Certa, National Pact for Literacy at the Right Age, (PNAIC) and the possibilities of enhancement beyond the verbal area. Theoretical material considered are based on studies related to: alphabetization and verbal literacy, in conformity with Soares (2004), Kleiman (1995) and Tfouni (1995); didactic sequence in line with Marcuschi (2008), Dolz, Noverraz, Schneuwly (2004); contemporary reader according to Santaella (2014); multiliteracy of Rojo (2013); literary literacy as systematic methodology Cosson (2014); and visual literacy in accordance with Panozzo (2007). In addition to these scholars, the Notebooks for Teacher Training of the Pact was studied and the literary collection for reading in the classroom for year three was analysed, made available by the Ministry of Education. The research methodological outline took on a qualitative approach, of the research-action type in a regular class of students of year three of Elementary School in a State School in the Serra region, in the state of Rio Grande do Sul. A descriptive analysis of mediums for continued formation of literacy teachers of PNAIC took place, by identifying the didactic exploration of books of infant literature restricted to verbal language dimension. The study of the literary collection made available for the year three of the literacy cycle reveals its characteristics as a verbal, visual and literary set. One title of this collection was selected and explored in didactic planning and application, under the optics of literacy, for showing potential characteristic for such. Obtained data show that visuality is a relevant aspect to attribute meaning to the literary text. It is possible to highlight the importance of teacher mediation in answer to the guiding question of the investigation, directed to the pedagogical planning, in the literacies perspective. This concept guides a more embracing exploration of the systems that compose an infant literature book and give opportunity for dialogue with life, the others and the world. Didactic mediation, guided this way, enhances textual comprehension, qualifies reading, speaking, writing, develops shared critics, in addition to supplying subsidies to teachers‟ formation quality.
O desafio da prática alfabetizadora na perspectiva dos letramentos visual e literário originou este trabalho. A discussão tem por objetivo central identificar os princípios subjacentes às sequências didáticas, propostas pelo Pacto Nacional pela Alfabetização na Idade Certa (PNAIC), e as possibilidades de ampliação para além da área verbal. O aporte teórico sustenta-se em estudos sobre: alfabetização e letramento verbal, conforme Soares (2004), Kleiman (1995) e Tfouni (1995); sequência didática à luz de Marcuschi (2008), Dolz, Noverraz, Schneuwly (2004); o leitor contemporâneo segundo Santaella (2014); os multiletramentos a partir de Rojo (2013); o letramento literário conforme metodologia sistematizada por Cosson (2014); e o letramento visual de acordo com Panozzo (2007). Além desses teóricos, foram estudadas as orientações dos Cadernos de Formação para Professores do Pacto e analisado o acervo literário para leituras em salas de aula do terceiro ano, disponibilizado pelo Ministério da Educação. O delineamento metodológico da pesquisa assumiu a abordagem qualitativa, na modalidade de pesquisa-ação, em uma classe regular de alunos do terceiro ano do Ensino Fundamental de uma Escola Estadual da região da Serra do Rio Grande do Sul. Realizou-se uma análise descritiva das orientações para a formação continuada de professores alfabetizadores do PNAIC, identificando a exploração didática dos livros de literatura infantil restrita à dimensão da linguagem verbal. O estudo do acervo literário disponibilizado ao terceiro ano do ciclo de alfabetização revela suas características como conjunto constituído pelo verbal, visual e literário. Um título desse acervo foi selecionado e explorado em planejamento didático e aplicação, sob a ótica dos letramentos, pelas suas características potenciais para tanto. Os dados obtidos demonstraram que a visualidade é um aspecto relevante para a atribuição de significados ao texto literário. Destaca-se a importância da mediação docente em resposta à pergunta norteadora da investigação, dirigida ao planejamento pedagógico, na perspectiva dos letramentos. Esse conceito guia uma necessária exploração mais abrangente dos sistemas que compõem e oportuniza um livro de literatura infantil e que oportunizam o diálogo com a vida, os outros e o mundo. A mediação didática, assim orientada, amplia a compreensão do texto, qualifica a leitura, a oralidade, a produção escrita, desenvolve a crítica compartilhada, além de fornecer subsídios para a qualidade da formação docente.
Keywords: Letramento; Leitura; Alfabetização; Literatura infantil; Educação de crianças; Literacy; Reading; Children's literature; Education of children